Pharmacokinetics of amphotericin B after accidental overdose in an adult critically ill patient treated with plasmapheresis: a case report and review of literature - Van Oers, Jos A. H.; Workum, Jessica D.; Voorzaat, Bram M.; Jaspers, Tessa C. C. (International Journal of Basic & Clinical Pharmacology, 2024)
Amphotericin B is a broad-spectrum antifungal agent that is used in the treatment of systemic fungal infections. We describe the case of a 62-year-old female patient with recent aneurysmal subarachnoid hemorrhage who was treated for suspected ventriculitis and a fungal coinfection. Instead of liposomal amphotericin B (L-AmB), 465 mg (5 mg/kg) amphotericin B deoxycholate (DOC) was inadvertently administered, leading to refractory shock with multiple organ failure and requiring mechanical ventilation. Since an overdose of amphotericin B can lead to fatal consequences and has a half-life of 15 days, plasmapheresis was started. The serum concentration decreased from 1.32 µg/mL to 0.62 µg/mL before plasmapheresis, demonstrating a mean half-life of 49 hours. After two plasmapheresis sessions, the serum concentration further dropped to 0.26 µg/mL, demonstrating a mean half-life of 17 hours. In contrast, the third plasmapheresis session had no effect on serum concentration. The patient made a full recovery, potentially facilitated by enhanced amphotericin B elimination through plasmapheresis. Positive outcomes were previously reported in two adult patients treated with plasmapheresis. However, other reports without plasmapheresis described fatal outcomes in adult patients, albeit with a twofold overdose compared to the two patients successfully treated with plasmapheresis. Moreover, plasmapheresis itself carries risks such as hypocalcemia, metabolic alkalosis, and coagulation deficits. Consequently, the role of plasmapheresis in amphotericin B overdose is still debated.